Influence of the interphase between laser-cladded metal layer and steel substrate on fatigue propagation of a short edge crack - Lucie Malikova; Pavel Doubek; Petr Miarka; Stanislav Seitl (Fracture and Structural Integrity)
Laser cladding is a relatively new technology how to combine properties of various materials. Thus, bi-material interfaces are presented in real structures and can affect the fatigue crack propagation. A cracked bar subjected to pure tensile loading is numerically simulated in this work in order to analyze the effect of the interphase layer between the cladded metal layer and the steel substrate on crack growth in the surface layer. Particularly, the influence of various Young’s modulus of the interphase on the stable/unstable edge crack propagation is assessed. Moreover, the number of cycles necessary for achievement of the defined critical crack length is calculated and it is summarized that knowledge of elastic properties of the thin interphase is crucial for fracture and fatigue analyses.